A miniaturized aerosol sizing sensor using light-scattering angular spectrum. (January 2023) - Zeng, Jin; Bian, Ang; Chen, Ang; Xu, Wenbo; Cheng, Wenqing; Yan, Shu; Wang, Shu; Deng, Tian
Highlights: Light-scattering angular spectrum is proposed for high-resolution particle sizing. A compacted and lens-free optical system is designed for LSAS sampling. The particle size distribution is inversed with high accuracy ( DKL < 0.05). The sensor is low-cost and portable for in-situ aerosol contamination measurement. Abstract: In the study of aerosols, great concern has been focused on the particle size distribution (PSD) as a crucial factor of the physical and chemical properties of the aerosols. There are strong and growing demands for on-line and in-situ aerosol analysis technologies, but existing portable aerosol sensors can hardly provide high-resolution and accurate PSD measurement with limited volume and cost. To address this challenge, we introduce the concept of a new optical aerosol sensing method using light-scattering angular spectrum (LSAS), which describes the angular dependence of the scattering light intensity. The key novelty is a compacted LSAS sampling module for collecting the scattering light up to the observing angles. According to the wide-range LSAS sampled by our sensor, high-resolution PSD is predicted by non-negative regularization inversion algorithm. To validate the performance of our sensor, monodisperse di-ethyl-hexyl-sebacate aerosols (DEHS) samples of different sizes and smokes of smoldering cotton rope were tested. The maximum relative error ( RE ) of LSAS was smaller than 12.02%, while the Kullback-Leibler Divergence ( DKL ) between inversed and reference PSDs were smaller than 0.05. Without using any particulate pre-separation module and optical lens, we build a novel low-cost and miniaturized sensor only composed of a mirror, a linear charge coupled device (CCD) and a semiconductor laser, which has significant potential for high-resolution aerosol sizing in routine field measurements outside a laboratory.